Implementasi Model Waterfall Pada Sistem Informasi Pengiriman Barang Berbasis Web - Susafaati Susafaati (JURNAL TEKNIK KOMPUTER, 2019)
Abstract— Shipping goods systems is still done manually, from serving customers until data storage which related to shipping process  of making a report, so errors  in registration, less accurate and delay report of required data  is occurs. information system design is the best solution to solve the existing of shipping goods, as well as with the computerized system which is effective and efficient to support activities on the Web shipping item. Keywords: shipping goods system, Web.